Information Technology Governance Audit Using the COBIT 5 Framework (Case Study of PDAM Tirta Patriot Kota Bekasi) - Lisda Awalia Aprilianti; Eko Darwiyanto; Yanuar Firdaus Arie (Indonesia Journal on Computing (Indo-JC), 2021)
PDAM Tirta Patriot has implemented information systems for its business process but still has deficiencies, including some business processes that do not have documented guidelines and procedures. Furthermore, the human resources in PDAM Tirta Patriot are insufficient for improving IT governance due to the lack of reliable personnel in the IT unit. Given the importance of IT for PDAM, an audit is needed to evaluate the capability of the IT unit in managing IT. COBIT 5 provides a goals cascade to align the company with its business goals. However, the goals cascade does not provide priority to IT-related goals. Therefore, for prioritizing IT-related goals, this research uses Analytical Hierarchy Process (AHP). From the AHP result, the selected domains are APO01, MEA01, and APO07. This research aims to determine the current capability level and analyze the gap between it and the chosen target capability level, precisely level 2. The current capability level of PDAM Tirta Patriot from domain APO01 is 1, MEA01 is 0, and APO07 is 0, which means none of those have reached the target capability level. Recommendations are given based on the unfulfilled work product for domains that do not reach the target capability level.